2021
DOI: 10.3390/ijerph18158144
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Levels Predict Bone Mineral Density in Postmenopausal Women Undergoing Oral Bisphosphonates: A Two-Year Follow-Up

Abstract: Clinical psychological factors may predict medical diseases. Anxiety level has been associated with osteoporosis, but its role on bone mineral density (BMD) change is still unknown. This study aimed to investigate the association between anxiety levels and both adherence and treatment response to oral bisphosphonates (BPs) in postmenopausal osteoporosis. BMD and anxiety levels were evaluated trough dual-energy X-ray absorptiometry and the Hamilton Anxiety Rating Scale (HAM-A), respectively. Participants receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Higher anxiety levels could also contribute to the development of an adequate adherence to medical treatment in post-menopausal osteoporotic women ( 20 ). It is known that a lower adherence exposes patients to a poorer treatment response and to a worst BMD ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher anxiety levels could also contribute to the development of an adequate adherence to medical treatment in post-menopausal osteoporotic women ( 20 ). It is known that a lower adherence exposes patients to a poorer treatment response and to a worst BMD ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…These variables allowed, through a computer-based algorithm (FRAX ® , http://www.shef.ac.uk/FRAX , accessed at the time of recruitment) ( 36 ), to evaluate the probability of major osteoporotic and hip fractures within the next 10 years. At baseline and after a 2-year follow-up, the levels of anxiety, depression and HRQoL were assessed through a gold standard psychological interview ( 20 ). The Hamilton Anxiety Rating Scale (HAM-A) was administered to detect the entity of anxious symptoms, through the scoring of 14 items (assessed from 0, not present, to 4, severe) which are based on psychological and somatic symptoms (anxiety, tension, fear, insomnia, intellectual impairment, depression, somatic symptoms, sensory, cardiovascular, respiratory, gastrointestinal, genitourinary, autonomic diseases, and observed behavior during the interview.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2010 report demonstrated an association between the bisphosphonates as a class and depressive symptoms in humans, reporting a reported odds ratio (ROR) of 2.3 (2.1–2.5) in WHO database, while in was not significant for alendronate 1.3 (0.7–2.5) in the Lareb database 14 . Interestingly, a longitudinal study of osteoporosis patients revealed that anxiety was as an independent predictor of bone mineral density 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Life expectancy is increasing world-wide, thus age-related diseases are becoming a major health concern. Chronic diseases and related outcomes, such as osteoporosis and associated fractures, diabetes, endocrine, and cardiovascular disease, may seriously impact people's quality of life and their perceived quality of life (Guicciardi, 2017 ; Marchetti et al, 2017 ; Catalano et al, 2020 ; Vita et al, 2020 ; Di Bari et al, 2021 ; Martino et al, 2021a , b , c ). This impact may, in turn, lead to psychopathological consequences (Di Giuseppe et al, 2020a ; Giusti et al, 2021 ).…”
mentioning
confidence: 99%